FEATURES OF RAISING CHILDREN IN DIVORCED AND SINGLE-PARENT FAMILIES - Amanzhol Kalysh; Ainara Galymkyzy (Progress in Science, 2023)
The family is considered the main institution that has a historical role as the main focus of personality formation. Family relationships and behavioral roles are the main means of socialization of children. Attention is also paid to the differences in the socialization of children and adolescents in single-parent families. The main emotional and material problems of children and adolescents that we face today and their consequences were analyzed. The intra-family relations with such parents and the peculiarities of their functioning are also considered. The article also traces the contrasts of the appearance of the families studied by us as a result of the termination of registered marriages.